EMPLOYABILITY ANALYSIS OF SOCIAL WORK GRADUATES AS HUMAN RESOURCES PRACTITIONERS IN INDUSTRIES - Omar, Fikran; Suriadi, Agus (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This study aims to determine whether a social work graduate has a large or small chance of being eligible to be a human resources practitioner in the industry. This research is qualitative and uses data collection techniques through library studies, internet-based research, as well as field studies that included interviews and observations with practitioners of human resources from Ralali.com, Unilever Indonesia, Glints Indonesia, and TikTok (Bytedance) Indonesia. Based on the results of the study, the authors concluded that the opportunity for social work graduates to become practitioners in human resources feasibility exists. In the discussion, the factors that influence the magnitude of the opportunity are: first, the views of human resources practitioners in the industry towards social work graduates are still not optimal, but when human resources practitioners already know in detail about social work and its graduates, practitioners tend to believe in the skills possessed by social work graduates. Second, it shows how the industry is actually quite open to hiring graduates of any education for positions in human resources as long as these graduates possess the competencies required by the industry even though the level of market competition for positions in human resources is quite competitive.  Keywords: Employability, Human Resources, Human Resources Practitioners, Social Work Graduates, Industry